Temporal Dynamics and Motivations for Urban Community Food Gardens in Medium-Sized Towns of the Eastern Cape, South Africa - Sky Roberts; Charlie Shackleton (Land, 2018)
Urban agriculture is said to be increasing with global urbanization. However, there is little examination of the temporal or spatial dynamics of urban agriculture. We investigated the benefits and challenges experienced by community gardeners in four towns in South Africa, along with GIS analysis of the number, area, and location of urban food community gardens over the last three decades. Common reasons for practicing community gardening were cash poverty (37%) and the need to grow food (34%). The most common benefits reported by respondents were a healthy lifestyle (58%) and consumption of the food produced (54%). Theft of garden infrastructure or produce was a noteworthy challenge to continued motivation and engagement in urban community gardening. There were declines in the number and area of urban community gardens, and more central location over the last three decades. Only 16% of the gardens present in the 1980s were still operating in the 2000s. Clearly community gardening is temporally and spatially dynamic, which requires context-sensitive policy initiatives.